KEBIJAKAN PEMERINTAH DALAM MENGATASI KELANGKAAN MINYAK GORENG PADA MASA PANDEMI COVID-19 DALAM PERSPEKTIF EKONOMI ISLAM - Hidayat, Ahmad Agus; Mustofa, Mustofa; Arlina, Agustin Mila (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2023)
In this study, the aim was to find out the policies implemented by the government in overcoming the scarcity of cooking oil during the Covid-19 pandemic in an Islamic economic review. This research resulted in a policy implemented by the government to restore cooking oil prices and ensure people's purchasing power which includes (1) regulating packaged cooking oil subsidies through (BPDPKS) (2) Setting the Highest Retail Price (HET) through Permendag no 6 of 2022 (3 ) Domestic Market Obligation (DMO) and Domestic Price Obligation (DPO) policies (4) Market intervention policies carried out by the government in overcoming the scarcity of cooking oil during the Covid-19 pandemic are following the principles of Maqashid Syariah because they aim to benefit and avoid harm. (5) Through the policies implemented by the government during the time of scarcity of cooking oil, corresponding to the phenomenon that occurred during the time of Abu Yusuf where he denied the theory of demand and supply, in which the price was not only affected by the aspect of demand but also depended on the power of bidding aspect.